Evaluating the Impact of LKPP Regulation No. 7 of 2021 on the Optimization of Functional Positions in Papua’s Procurement Bureau - Rumasukun, Muchammad Amin; Risamasu, Ferdinand; Kambu, Arius Andreas (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study aims to analyze the implementation of LKPP Regulation No. 7 of 2021 on the optimization of functional positions of procurement officers (JF PPBJ) in the Bureau of Procurement of Goods and Services, Regional Secretariat of Papua Province. The regulation was introduced to strengthen the professionalism of civil servants and improve the quality of procurement governance at the regional level. However, in practice, there remains a gap between regulatory mandates and their implementation in the field. The research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and document review, and analyzed using NVivo 12 Plus software for thematic coding and data organization. Data validity was ensured through source and method triangulation. The findings indicate that functional officers perform only part of their mandated duties, particularly in supplier selection and technical assistance during the planning stage, while their roles in contract management and self-managed procurement remain limited. Nevertheless, the annual credit target as a performance indicator was consistently achieved, reflecting a selective and adaptive form of optimization. Supporting factors include adequate facilities, incentives, and inter-agency coordination, while inhibiting factors involve budget constraints, external interventions, and the limited readiness of local providers. This study concludes that the optimization of functional positions is not solely determined by formal compliance with regulatory tasks but also by the bureaucracy’s ability to adapt to practical conditions in the field. The findings imply the need to strengthen coordination, enhance capacity building, and revise performance indicators so that functional officers can contribute more substantively to the effectiveness, efficiency, and transparency of public procurement.